PARTITION FUZZY DOMAIN WITH MULTI-GNANULARITY REPRESENTATION OF DATA BASING ON HEDGE ALGEBRA APPROACH - Anh, Nguyễn Tuấn; Sơn, Trần Thái (Journal of Computer Science and Cybernetics, 2018)
The article presents methods of dividing quantitative attributes into fuzzy domainswith multi-gnanularity representation of data, basing on hedge algebra approach. With this approach,explored association rules will express more information, from general to specic knowledge, thanusing usual single-granularity representation of data. At the same time, as a consequence, the numberof exploring rules will be more, meeting the needs of the user